PENGAWETAN KAYU KELAPA DENGAN METODE RENDAMAN DINGIN - Barly Barly; Sasa Abdurrochim (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
A study on the treatability of coconut trunk was carried out using the cold soaking method with Formula 7, Wolmanit CB and Diffusol CB as preservatives. The specimens size 50cm x 5cm x 5cm were soaked in five percent pre- servatives solution for period of one, three, five and seven days. The preservatives retention and penetration were re- corded. From this study the following conclusions could be drawnThe densities and treatment schedule have a significant bearing on the preservatives penetration and retention.Both factors have significant interaction effect on preservatives retention and penetration. This implies that the densities should be taken into account in determining the effectivity of a treatment schedule.